Sex differences in sympathetic activity in obesity and its related hypertension. Issue 1 (14th May 2019) - Fu, Qi
Abstract: The prevalence of obesity is rapidly increasing in the United States, particularly among women. Approximately 60−70% of hypertension in adults may be directly attributed to obesity. In addition, maternal obesity is a major risk factor for hypertensive disorders during pregnancy. The underlying mechanisms for the association between obesity and cardiovascular risk are multifactorial, but activation of the sympathetic nervous system is one significant contributing factor. This brief review summarizes the current knowledge on sex differences in sympathetic activity in obesity and its related hypertension, with a focus on studies in humans. Evidence suggests that abdominal visceral fat, rather than subcutaneous fat, is related to augmented sympathetic activity regardless of sex. Race/ethnicity may affect the relationship between obesity and sympathetic activity. Obesity‐related hypertension has an important neurogenic component, which is characterized by sympathetic overactivity. However, sex may influence the association between hypertension and sympathetic overactivity in obese people. Finally, both body weight and sympathetic overactivity seem to be involved in the development of gestational hypertensive disorders in women. Chronic hyperinsulinemia due to insulin resistance, high plasma levels of leptin, and/or obstructive sleep apnea may be responsible for sympathetic overactivity in obesity‐related hypertension. Abstract : This brief review summarizes the current knowledge on sex differences in resting muscle sympathetic nerve activity and organ‐specific (e.g., renal and cardiac) norepinephrine spillover in obesity, as well as its related hypertension. The focus of this review is largely on literature specific to human studies.